Downward Movement of Potentially Toxic Elements in Biosolids Amended Soils - Silvana Irene Torri; Rodrigo Studart Corrêa (Applied and Environmental Soil Science)
Potentially toxic elements (PTEs) in soils are mainly associated with the solid phase, bound to the surface of solid components, or precipitated as minerals. For most PTEs, only a small portion is dissolved in the soil solution. However, there is an interest in following the fate of mobile PTEs in the environment, for a growing amount of evidence indicates that downward movement of PTEs may occur in biosolids amended soils, leading to groundwater contamination. Therefore, it is crucial to understand the factors that control the release of these elements after land application of biosolids, in order to overcome problems related to downward movement of PTEs in the soil profile.